Anteseden Loyalitas Pelanggan E-commerce - Yanti, Ni Putu Dian Ariyani Padma; Wimba, I Gusti Ayu; Putra Astawa, I Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This research was conducted with the aim of knowing the effect of service convenience on loyalty directly and through mediation of customer satisfaction. The research location is set in Denpasar City for the number of people who are Lazada customers who are not known for certain. Determination of the sample was carried out by considering 5 times the number of indicators so that a sample of 160 people was determined using purposive sampling and convenience sampling. Data was collected through interviews at the pre-survey stage and questionnaires using a five-choice Likert Scale. The instrument test was carried out by testing the validity and reliability and continued with hypothesis testing using path analysis test and Sobel test to test the mediating role of customer satisfaction. The results of the analysis prove that service convenience has a positive and significant effect on customer satisfaction and loyalty, customer satisfaction has a positive and significant effect on customer loyalty, and customer satisfaction mediates the effect of service convenience on customer loyalty